Factors Influencing Developers' Acceptance of Native Development Environments: An Expansion of the Technology Acceptance Model - Nadja Ganter (Junior Management Science (JUMS), 2021)
Mobile operating systems opening up their development environments to third-party developers evoke skyrocketing supply of mobile applications. This study investigates factors influencing the acceptance of third-party developers to adopt native development environments for creating mobile apps. Based on an extensive literature review, the author proposes a research model, built on the technology acceptance model created by Davis. Through the data collected from an online questionnaire completed by third-party app developers, the model was tested using structural equation modeling. Findings indicate a significant effect of the proposed constructs: self-efficacy, output quality, subjective norm, perceived enjoyment, perception of external control, developer community and training. This analysis confirms that the intention to use a native development environment is significantly affected by perceived ease of use and perceived usefulness, whereby the effect size of perceived usefulness is noticeably stronger. Managerial implications suggest to promote high usefulness rather than primarily focusing on an easy to use interface.
Keywords: 650; Native development environment; third-party develope; mobile app development; technology acceptance